Distinct Contributions of Neutrophils and CCR2 + Monocytes to Pulmonary Clearance of Different Klebsiella pneumoniae Strains - Xiong, Huizhong; Carter, Rebecca A.; Leiner, Ingrid M.; Tang, Yi-Wei; Chen, Liang; Kreiswirth, Barry N.; Pamer, Eric G. (Infection and immunity, 2015)
Klebsiella pneumoniae is a common respiratory pathogen, with some strains having developed broad resistance to clinically available antibiotics. Humans can become infected with many different K. pneumoniae strains that vary in genetic background, antibiotic susceptibility, capsule composition, and mucoid phenotype. Genome comparisons have revealed differences between K. pneumoniae strains, but the impact of genomic variability on immune-mediated clearance of pneumonia remains unclear. Experimental studies of pneumonia in mice have used the rodent-adapted 43816 strain of K. pneumoniae and demonstrated that neutrophils are essential for optimal host defense. It remains unclear, however, whether CCR2 + monocytes contribute to K. pneumoniae clearance from the lung. We selectively depleted neutrophils, CCR2 + monocytes, or both from immunocompetent mice and determined susceptibility to infection by the 43816 strain and 4 newly isolated clinical K. pneumoniae strains. The clinical K. pneumoniae strains, including one carbapenem-resistant ST258 strain, are less virulent than 43816. Optimal clearance of each of the 5 strains required either neutrophils or CCR2 + monocytes. Selective neutrophil depletion markedly worsened infection with K. pneumoniae strain 43816 and three clinical isolates but did not increase susceptibility of mice to infection with the carbapenem-resistant K. pneumoniae ST258 strain. Depletion of CCR2 + monocytes delayed recovery from infection with each of the 5 K. pneumoniae strains, revealing a contribution of these cells to bacterial clearance from the lung. Our findings demonstrate strain-dependent variation in the contributions of neutrophils and CCR2 + monocytes to clearance of K. pneumoniae pulmonary infection.